Additional CTA-Subtraction Technique in Detection of Pulmonary Embolism—a Benefit for Patients or Only an Increase in Dose?. Issue 1 (July 2020) - Nestler, Kai; Becker, Benjamin Valentin; Majewski, Matthäus; Veit, Daniel Anton; Krull, Bastian Felix; Waldeck, Stephan
Abstract : Abstract: Latest advantages in computed tomography (CT) come with enhanced diagnostic imaging and also sophisticated dose reduction techniques. However, overall exposure to ionizing radiation of patients in Germany rises slightly, which is mainly based on the growing number of performed CT scans. Furthermore, new possibilities in modern imaging, including 4D scans or perfusion protocols, offer new medical insights but require additional scans. In this study, we reevaluated data sets from patients undergoing CT examinations because of suspected pulmonary embolism and compared doses and diagnostic results of the standard protocol to the additional modern CT subtraction technique. Two groups of single-blinded radiologists were provided with CT data sets from 50 patients. One group (G1) had access to full datasets including CT subtraction with perfusion map. The other group (G2) only evaluated conventional CT angiography. Results were compared to final clinical diagnosis. Dose length product (DLP) of CT angiography was compared to CT subtraction technique, which consists of an additional non-contrast-enhanced scan and perfusion map. Effective dose was calculated using a Monte Carlo simulation-based software tool (ImpactDose). Inter-rater agreement of both groups was strong in G1 with κ = .896 and minimal in G2 (κ = .307). Agreement to final diagnosis was strong in both groups (G1, κ = .848; G2, κ = .767). Doses applied using the CT subtraction technique were 34.8% higher than for CT angiography alone (G1 DLP 337.6 ± 171.3 mGy x cm; G2 DLP 220.2 ± 192.8 mGy x cm; p < .001). Calculated effective dose was therefore significantly higher for G1 (G1 4.82 ± 2.20 mSv; G2 3.04 ± 1.33 mSv; p < .001). Our results indicate a benefit of the CT subtraction technique for the detection of pulmonary embolisms in clinical routine, accompanied by an increase in the dose administered. Although CT protocols should always be applied carefully to specific clinical indications in order to maximize the potential for dose reduction and keep the administered dose as low as reasonably achievable, one should never lose sight of the diagnostic benefit, especially in vital clinical indications.